Immune perturbations in HIV-1–infected individuals who make broadly neutralizing antibodies - Moody, M; Pedroza-Pacheco, I; Vandergrift, N; Chui, C; Lloyd, K; Parks, R; Ogbe, A; Cohen, M; Liao, H; Gao, F; McMichael, A; Montefiori, D; et al. (American Association for the Advancement of Science, 2016)
Induction of broadly neutralizing antibodies (bnAbs) is a goal of HIV-1 vaccine development. bnAbs occur in some HIV-1–infected individuals and frequently have characteristics of autoantibodies. We have studied cohorts of HIV-1–infected individuals who made bnAbs and compared them with those who did not do so, and determined immune traits associated with the ability to produce bnAbs. HIV-1–infected individuals with bnAbs had a higher frequency of blood autoantibodies, a lower frequency of regulatory CD4+ T cells, a higher frequency of circulating memory T follicular helper CD4+ cells, and a higher T regulatory cell level of programmed cell death–1 expression compared with HIV-1–infected individuals without bnAbs. Thus, induction of HIV-1 bnAbs may require vaccination regimens that transiently mimic immunologic perturbations in HIV-1–infected individuals.